The Muses Revise the Canon: Romantic Women Writers Facing the Construction of a (New) Identity in the Mid-19th Century - Estefanía Cabello (Estudios de Teoría Literaria)
In her correspondence, Gertrudis Gómez de Avellaneda refers several times to the work of Saint Teresa as an image of her own; Carolina Coronado also dedicates an extensive essay to her, published in the Semanario Pintoresco Español in 1850. At this moment, Coronado is also composing an interesting novel dedicated to Luisa Sigea. The Mexican Josefa Sanromán, a contributor to La Ilustración. Álbum Universal (1849-1857), painted a self-portrait in the background of which Saint Teresa can be seen inspiring her creation. Through their revision of texts linked to the previous canon, these female writers helped to construct a new concept of female authorship —or multiple conceptions of female authorship— at a time when their genealogy and history had not yet been created. In this article, I analyze the texts that appeared in the middle century press such as La Ilustración (1849-1857), La Discusión (1856-1887) or Semanario Pintoresco Español (1836-1857). These texts conclude in the union of these female authors with the previously established canon to shape the identity of each one and their genre. A literary overview of this renewed approach to women's writing and the construction of a (new) identity for 19th-century women authors.